HEREDITARY AS A CAUSE AND CONDITION OF THE DEVELOPMENT OF THE DISEASES - Hryshko, Yu.M. (World of Medicine and Biology, 2016)
Human being is a part of the biosphere and the evolution of its product, so the patterns of biological processes that have universal value, fully apply to humans. In addition pathogenic environmental factors in the development of human diseases significant role played by genetic factors. Thus, the laws of heredity and variation, clarified the general genetics for many more ordinary objects can be fully transferred to the person and its population. Knowledge of human genetics, detailed study of the family tree with people seeking advice, allowing geneticists to assess risk in each case.
Keywords: disease; heredity; genetics